A Canadian perspective on cannabis normalization among adults - Duff, Cameron; Asbridge, M.; Brochu, S.; Cousineau, M.; Hathaway, A.; Marsh, D.; Erickson, P. (2012)
Once associated with 'deviant' subcultures, the use of cannabis is now common across Canadian society. This has led some to argue that cannabis use is becoming normalized in Canada with important implications for drug policy, law enforcement and public health. This article takes up these issues, reporting the results of a qualitative study involving 165, socially integrated, adult cannabis users in four Canadian cities (Vancouver, Montreal, Toronto and Halifax). The aims of this study were twofold; first, we sought to contribute to recent efforts to extend the analysis of normalization and its associated features from adolescent and young adult populations to older adults, with a particular focus on cannabis. Second, we wished to respond to recent calls for greater analysis of both the social and structural determinants of normalization, as well as its contingent, 'micro-level' features. Our examination of these diverse dimensions revealed significant changes in the meaning and status of cannabis use in Canada. Although some social and personal stigmas remain, our research suggests they are largely confined to the immoderate, 'irresponsible' use of cannabis, while more 'controlled' use among adults appears all but de-stigmatized. This process has involved changes in the ways risks associated with cannabis use are characterized and managed; shifts in the ways adult cannabis users seek to moderate their use; as well as broader social and cultural shifts in the meanings associated with cannabis in Canada. We conclude with a discussion of the potential impacts of these developments for drug policy debates in Canada and elsewhere. © 2012 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.